THE USE OF ONLINE GAME AS MEDIA TO MOTIVATE LEARNING VOCABULARY IN ENGLISH DURING PANDEMIC AT BAN LOEI WANGSAI SCHOOL THAILAND - Sarah masyitha elysia; Candra Hadi Asmara (English Journal Literacy Utama, 2022)
This observation ambitions to decide the extent of scholar motivation toward online games in enhancing getting to know English  approximately  vocabulary.  This observation  carried  out at Ban Loei Wangsai School Thailand. The researcher had 15 students as respondents. The writer uses a qualitative descriptive method with the theories from (Creswell, 2012).The writer also used the theories about the online game to motivate learning vocabulary from Ashraf et al (2014), (Mahmut Kayaalti, 2018) and (Okaz, 2014). Based in the result, it can be visible that college students motivation as 80% of respondents agree  that online games encourage college students in getting to know vocabulary, 93% online games are useful tools to be applied in learning vocabulary, 87% online games are effective tools to be applied in learning vocabulary, 73% online games make learning vocabulary more interesting, 87% learning vocabulary using online games become more enjoyable, 67% online games can increase positive feeling, 80% online games can reduce  anxiety, 87% online games improve self-confidence in learning vocabulary, 93% learning vocabulary using  online  games  based can create a fun  atmosphere  in  the classroom, 73%  online games is a useful tool for improving vocabulary.